2018
DOI: 10.1186/s12891-018-2221-5
|View full text |Cite
|
Sign up to set email alerts
|

Persistent synovial inflammation plays important roles in persistent pain development in the rat knee before cartilage degradation reaches the subchondral bone

Abstract: BackgroundThe major complaint of knee osteoarthritis (OA) is persistent pain. Unlike acute inflammatory pain, persistent pain is usually difficult to manage since its pathology is not fully understood. To elucidate the underlying mechanisms of persistent pain, we established 2 different inflammation-induced arthritis models by injecting monoiodo-acetic acid (MIA) into the joint cavity and performed integrated analyses of the structural changes in the synovial tissue and articular cartilage, sensory neuron rear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 33 publications
(30 reference statements)
2
46
0
2
Order By: Relevance
“…On the other hand, we have shown that joint damage and pain behavior develop similarly after DMM in both male and female C57/BL6 mice [132]. However, TRPV-1 antagonist capsazepine significantly reduced DMM-induced pain and the expression of TRPV-1 in DRG only in male mice [103]. In another study that used DMM in C57BL/6 mice, although OA changes were evident in 12-month-old females, the extents of cartilage degradation, subchondral bone plate sclerosis, and osteophytes were milder than in males [78].…”
Section: Mnx (2 Wk)mentioning
confidence: 81%
See 1 more Smart Citation
“…On the other hand, we have shown that joint damage and pain behavior develop similarly after DMM in both male and female C57/BL6 mice [132]. However, TRPV-1 antagonist capsazepine significantly reduced DMM-induced pain and the expression of TRPV-1 in DRG only in male mice [103]. In another study that used DMM in C57BL/6 mice, although OA changes were evident in 12-month-old females, the extents of cartilage degradation, subchondral bone plate sclerosis, and osteophytes were milder than in males [78].…”
Section: Mnx (2 Wk)mentioning
confidence: 81%
“…The collagenase-induced OA (CIOA) model, which is induced by chemical instability resulting from intra-articular injection of collagenase, also exhibits pronounced synovitis and early exhibition of thermal hyperalgesia, manifesting as early as 1 week after injection [61], while DMM mice do not exhibit thermal hyperalgesia until the late phase of the disease [95]. Persistent inflammation with fibrosis in the synovial tissue of MIA model was accompanied by pain avoidance behavior before articular cartilage degeneration and by an increase in calcitonin gene-related peptide (CGRP)-positive fibers in the DRG and synovium [103]. CIOA induced an increase in interferon regulatory factor 4 (IRF-4), CCL-17 and chemokine (c-c motif) receptor 4 (CCR-4), the CCL-17 receptor; gene-deficient mice were protected from pain as well as joint destruction, indicating that these molecules are required for the development of OA pain [104].…”
Section: Mnx (2 Wk)mentioning
confidence: 99%
“…Intra-articular injection of MIA is a well-characterized animal model for inflammation-induced OA [811]. By using this model, we have reported two different inflammation-induced articular cartilage degeneration models in rats [12, 13]. One is the low-dose model (0.2 mg), in which acute inflammation was observed within 3 days, peaked at 5 days, then alleviated after 7 days [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…By using this model, we have reported two different inflammation-induced articular cartilage degeneration models in rats [12, 13]. One is the low-dose model (0.2 mg), in which acute inflammation was observed within 3 days, peaked at 5 days, then alleviated after 7 days [12, 13]. In this model, we observed slow progression of articular cartilage degeneration after 28 days without apparent synovial inflammation after 14 days [12, 13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation